Anemia Biomarkers in Pregnant People with Pyelonephritis - Al-Shibli, Noor K.; Weaver, Kristin E.; Grace, Matthew R.; Kuller, Jeffrey A.; Heine, R. Phillips; Unnithan, Shakthi; Dotters-Katz, Sarah K. (American Journal of Perinatology, 2025)
Anemia is observed in 30% of pregnancies with pyelonephritis, yet little is known about the underlying etiology. Erythropoietin (EPO) is renally produced in response to hypoxic and inflammatory conditions. Changes in serum EPO have been demonstrated in infectious conditions in the nonpregnant population. EPO levels have been measured in healthy pregnancy cohorts, but little is known about patterns in the setting of renal inflammation. Our primary objective was to compare EPO levels in pregnant patients at diagnosis of acute pyelonephritis to established trimester-specific norms. Secondary objectives included assessing iron deficiency and hemolysis markers as alternate etiologies of anemia.Prospective cohort study of pregnant people aged ≥ 18 years diagnosed with pyelonephritis, defined as the presence of urinary tract infection symptoms plus flank pain, fever, or nausea/vomiting. Blood samples including EPO, iron, transferrin, lactate dehydrogenase (LDH), and haptoglobin were obtained within 72 hours of diagnosis. Demographics and clinical data were abstracted from medical records. Wilcoxon Signed-Rank test compared study EPO levels to noninfected pregnancy values established in the literature. Secondary outcomes included number of patients with iron/hemolysis laboratories within trimester-specific reference ranges.The study cohort included 17 patients with pyelonephritis in the second or third-trimester. There were no eligible first-trimester patients during the study period. Anemia was present on admission in 35.3% (6/17) of patients. EPO levels were significantly higher in pyelonephritis patients during the second-trimester compared with literature-established EPO levels in noninfected controls: 48.6 versus 10.6 mU/mL, (p = 0.0001). Secondary analysis demonstrated normal iron and haptoglobin levels in most patients, and normal LDH in all patients.EPO levels in pregnant pyelonephritis patients were significantly higher compared with trimester-specific normative levels established in the literature. Evaluation of iron and hemolysis studies showed inconsistent results but were often normal. This pilot study may suggest a relationship between ineffective erythropoiesis and renal inflammation in pregnancies complicated by pyelonephritis.
Keywords: anemia; erythropoietin; inflammation; pyelonephritis; urinary tract infection; hemolysis